UJI PUPUK PETROGANIK DAN GRAND K TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN KACANG TANAH (Arachis hypogaea L.) - Jack Swanri Pakpahan; Siti Zahrah; Sulhaswardi Sulhaswardi (UIR Press, 2019)
ABSTRACT This research was carried out at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University, Pekanbaru, from April to July 2019. The purpose of this study was to determine the effect of the interaction and main fertilizer of Petroganik and Grand K on the growth and production of peanut plants. The method used was a Completely Randomized Design which consisted of two factors. The first factor was P (Petroganik) and the second factor was K (Grand-K), each of which consisted of 4 levels of treatment so that there were 16 treatment combinations. Each treatment consisted of 3 replications, so there were 48 experimental plots, consisting of 12 plants and 3 plants as observational samples with the total number was 576 plants. Data from the latest observations were analyzed by variance (ANOVA) and further tested with the significant difference in honesty (BNJ) at the 5% significant level. The results showed the interaction of Petroganik and Grand-K fertilizers significantly affected plant height, relative growth rate and weight of 100 seeds. The best combination of treatment in the application of Petroganic fertilizer was 81 g/plot and Grand K fertilizer was 14 g/plot (P3K2). The main effect of real Petroganik fertilizer on all parameters of observation with the best treatment was the application of Petroganic fertilizer as much as 81 g/plot (P3). The main effect of Grand K fertilizer was significant on all parameters observed with the best treatment was the application of Grand K fertilizer of 14 g/plot (K2).